Abrasive Wear Resistance of Concrete in Connection with the Use of Crushed and Mined Aggregate, Active and Non-Active Mineral Additives, and the Use of Fibers in Concrete - Bodnárová, Lenka; Ťažký, Martin; Ťažká, Lucia; Hela, Rudolf; Pikna, Ondřej; Sitek, Libor (MDPI, 2020)
Virtually every concrete structure comes into contact with abrasive effects of flowing media or solids, which have a direct impact on the durability of concrete. An abrasive effect is most pronounced in transport or water management structures, and these structures are often designed for a significantly longer service life (usually 100 years). This research evaluates the influence of the filler component in terms of the type of aggregate and its mineralogical composition on concrete abrasion resistance. As part of the impact of the binder component, several concrete mixtures were produced using the same aggregate and maintaining the same strength class with the addition of different types of active and inert mineral additives. In other parts of the research, the effect of adding fiber reinforcement on the abrasion resistance of concrete was verified. Mutual connections and correlations in different age groups (7, 28 and 90 days) were sought for all obtained results. The abrasion resistance of the composite was monitored by using standard procedures, especially using a Böhm device. It was found that for good abrasion resistance of concrete, it is not necessary to produce concretes with high strength classes using often expensive mineral additives (microsilica) and quality aggregates, but the maturation time of the composite and its microstructure plays an important role.

Virtually every concrete structure comes into contact with abrasive effects of flowing media or solids, which have a direct impact on the durability of concrete. An abrasive effect is most pronounced in transport or water management structures, and these structures are often designed for a significantly longer service life (usually 100 years). This research evaluates the influence of the filler component in terms of the type of aggregate and its mineralogical composition on concrete abrasion resistance. As part of the impact of the binder component, several concrete mixtures were produced using the same aggregate and maintaining the same strength class with the addition of different types of active and inert mineral additives. In other parts of the research, the effect of adding fiber reinforcement on the abrasion resistance of concrete was verified. Mutual connections and correlations in different age groups (7, 28 and 90 days) were sought for all obtained results. The abrasion resistance of the composite was monitored by using standard procedures, especially using a Böhm device. It was found that for good abrasion resistance of concrete, it is not necessary to produce concretes with high strength classes using often expensive mineral additives (microsilica) and quality aggregates, but the maturation time of the composite and its microstructure plays an important role.
Abrasive Wear Resistance of Concrete in Connection with the Use of Crushed and Mined Aggregate, Active and Non-Active Mineral Additives, and the Use of Fibers in Concrete
Keywords: concrete composite; abrasion; type of aggregate; mineral additives; fiber; durability; concrete strength; concrete composite; abrasion; type of aggregate; mineral additives; fiber; durability; concrete strength